Tourism, real estate and traditional populations Conflicts and interests in relation to land ownership - Rodrigues, Lea Carvalho (2011)
The article discusses the concepts of land ownership in a small town of the coast of Ceará state. Based on a procedural perspective, attempts to show how this conception has changed over time, exposing the nuances of the process of transforming land into a commodity, in that locality, especially after the interference of a company focused on tourism. The empirical data used came from ethnographic research that is being done in the town of Tatajuba, located in the far-western coast of the state of Ceara, near the beach of Jericoacoara, a region prioritized within the scope of a major tourist route, having direct support from the Ministry of Tourism, the State governments of Ceará, Piauí and Maranhão, the cities situated along the tourism route, as well as Sebrae and the Bank of Northeast Brazil. Throughout the article it is shown how these recent changes undermine the perception of older inhabitants about the events that led to the situation of dispute, producing cleavages as the field of conflict and interest about property land defines itself.